I’jāz al-Quran Dan Konsep Kesepadanan Dalam Terjemahan: Penelitian Dari Pandangan Sarjana Barat Dan Muslim - Rosli, M.,; Abdullah, N.,; Abd. Rahman, L. (KUIS, 2024)
Malaysian authorities, especially the Ministry of Home Affairs (KDN) have set specific or standard requirements for any publication of the translation of Quranic meanings to include copies of original texts. This is due to a number of attempts to bring out a translation of the Quran without the Arabic text. In order to identify the significant presence of the original Arabic text of the Quran, hence the study will be focused through the views of Islamic and Western scholars on the concept of equivalence as was defined by Nida (1964) and Catford (1965). The study was conducted based on the descriptive analysis through the views of various modern translation scholars and early Islamic scholars on the concept of meaning. The survey found that eventhought Islamic scholars have not discuss the subject of translatability in detailed as was done by western scholars, however, it can be summarized that the views of Muslim scholars as al-Jahiz (1965) and Ibn Qutaibah (1973) since the 8th century is consistent with the general concept of equivalence that developed by Western scholars. The studies suggest in the process of translating, the translator should make an effort to understand the source text first before moving into a target text. Besides capturing the maximum possibilities of the features of the target language.